To Revolt or Not to Revolt: A Muslim Perspective on the Egyptian Experiment (American Journal of Islam and Society, 2011)
Although—with a long way to go—the eighteen-day demonstrations inEgypt from January 25, 2011 to February 11, 2011, which toppled PresidentHosni Mubarak will ultimately go down in history as one of the great revolutions.This event stands alongside the French Revolution (1789–1799)and the Russian Revolutions (1917–1918). Almost everybody will agreethat it was not a religiously motivated one, even though it was executedthrough an unprecedented cooperation between different religious groupsand affiliations. In fact, this revolution was inspired by social, political, andeconomic concerns.However, with the majority of the Egyptians being Muslim (perhaps,because of that), and despite being un-Islamic itself, the Mubarak regimecouldn’t resist both unleashing Islamic propaganda and appealing to Islamicsensibilities of the demonstrators in its effort to foil the demonstrations.Could or should these demonstrations have been thwarted by justifiableIslamic injunctions?This came through the Grand Mufti (the formal, highest Muslim authority)of Egypt, Dr. Ali Jum`ah, who made several pronouncements todiscourage Muslim youth and their families from continuing to participatein the demonstrations. This brings forward some important questions: arepeaceful demonstrations to remove a “despotic” leader and a “corrupt”government allowed (even if riddled with potential chaos)? Or shouldMuslims allow themselves to be ruled in perpetual tyranny and oppressionin order to foster a lack of obvious chaos (not peace; as a tyrannical rulecannot be peaceful to the people themselves in the first place)? This editorial ...